2018
DOI: 10.1002/eco.1978
|View full text |Cite
|
Sign up to set email alerts
|

Estimating evapotranspiration change due to forest treatment and fire at the basin scale in the Sierra Nevada, California

Abstract: We investigated the potential magnitude and duration of forest evapotranspiration (ET) decreases resulting from forest‐thinning treatments and wildfire in west‐slope watersheds of the Sierra Nevada range in California, USA, using a robust empirical relation between Landsat‐derived mean‐annual normalized difference vegetation index (NDVI) and ET measured at flux towers. Among forest treatments, the minimum observed NDVI change required to produce a significant departure from control plots with NDVI of about 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 33 publications
7
49
0
1
Order By: Relevance
“…(1,200-2,100 m) in the Kings River basin directly south (Goulden et al, 2012). Using the same top-down approach, Roche et al (2018) showed similar results to those in our study, in that thinning treatments reduced evapotranspiration in the American, but not in the Forest vegetation growth following treatment or fire disturbance also varies by forest type and disturbance event. Roche et al (2018) found that following wildfire, evapotranspiration in the central Sierra…”
Section: Model Transferabilitysupporting
confidence: 86%
“…(1,200-2,100 m) in the Kings River basin directly south (Goulden et al, 2012). Using the same top-down approach, Roche et al (2018) showed similar results to those in our study, in that thinning treatments reduced evapotranspiration in the American, but not in the Forest vegetation growth following treatment or fire disturbance also varies by forest type and disturbance event. Roche et al (2018) found that following wildfire, evapotranspiration in the central Sierra…”
Section: Model Transferabilitysupporting
confidence: 86%
“…Given the recent drought and associated tree mortality in the Sierra Nevada (Tree Mortality Task Force, ), contemporary studies have addressed the impacts of tree density reductions due to forest thinning or fire on ET and surface water availability (Boisramé, Thompson, Collins, & Stephens, ; Roche, Goulden, & Bales, ). We included fire return interval departure—an indicator of tree density relative to historic conditions and associated fuels loading and ET—to assess how meadow sensitivity varies among departure classes.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of meadows in watersheds with the majority of vegetation classified as departed due to decreased fire frequency (suggesting increased tree densities) relative to historical conditions was not detectably different from those in watersheds in which fire frequency is consistent with historic regimes. It is possible that any signal in these data may simply be overwhelmed by the strong environmental gradients that exist across the study area, as fire effects may differentially affect watershed‐scale ET rates across gradients of water availability (Roche et al, ). Moreover, fire return interval departures do not explicitly account for fire severity and thus may not necessarily be indicative of ET water use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has estimated ET amounts in the Sierra Nevada using water balance approaches (Henn, Painter, et al, 2018; Kattelmann & Elder, 1991) and regression relationships between eddy covariance flux tower measurements and satellite products (Fellows & Goulden, 2017; Goulden et al, 2012; Roche, Goulden, & Bales, 2018). These approaches focused on different applications but concluded that annual ET in the upper elevations of the Sierra Nevada ranged between 150 and 400 mm, with most of the losses occurring below tree line.…”
Section: Background and Methodsmentioning
confidence: 99%